Življenje v spreminjajoči se kitajski urbani pokrajini - Zhang, Juyong (Urbani izziv, 2012)
Dalian is the second-most important city in the southern part of Liaoning Province in northeast China. The city can trace its history back to the Qingniwa settlement. This settlement was occupied from 1858 until 1950 in succession by the British, Japanese and Russian Empires, with each imposing its own building styles on the city. However, from 1950, when the city was finally returned to China by the Russians, who had captured it from the Japanese during the Second World War, most of the imperial buildings and sites were lost to redevelopment within the city. The most dramatic changes have taken place since 1984, when the city was declared a Special Economic Zone, and particularly during the 1990s, when Bo Xilai became the mayor and introduced parks, extensive motorways and many traffic circles. At present, having lost most of its traditional built environment, Dalian is a modern citymarked by dramatic housing developments and dominated by multi-family high-rise buildings to accommodate its population of 5.72 million. In 2011, a survey was conducted among 400 inhabitants of the city to ascertain their perceptions concerning life in Dalian and the Dalian Development Zone, their living conditions and their level of satisfaction with their housing. From the survey, it was clear that the majority of the interviewees were uncertain about the variables concerning the structural quality of their housing units and the nature, quality and accessibility of the services provided. However, most of them indicated that public transport, open spaces, parks and recreational facilities were within easy reach of their housing units.
Keywords: architecture; arhitektura; Dalian; Kitajska; kvaliteta življenja; mesta; urbani razvoj; urbanism; urbanizem